Educational Website Utilization and Teacher Job Performance: Evidence from a Public Elementary School Cluster in a Rural Island Province in the Philippines - Salinas, Geraldine; Cutab, Gerlie (JPAIR Institutional Research, 2025)
This study explored the use of educational websites and their relationship to the job performance of public elementary school teachers in Sagay, Camiguin. Anchored on the Technology Acceptance Model (TAM), the study adopted a descriptive-correlational design involving complete enumeration of 61 teachers from seven elementary schools. Data were gathered using a validated questionnaire. Findings revealed that educational websites were widely used, especially for professional development and curriculum integration. However, their use for assessment and feedback remained moderate. Despite the high level of usage, Spearman’s rank correlation showed no significant relationship between website utilization and job performance, with only 2.7% of performance variation explained by website use. Further analysis using Kruskal-Wallis and regression tests found no significant influence of demographic factors such as age, teaching experience, and educational attainment on website utilization. Most teachers received an “Outstanding” performance rating, indicating that factors beyond website usage contribute to job performance. These results suggest that while educational websites support teaching, their measurable impact on performance is limited without addressing broader pedagogical, infrastructural, and institutional factors. To address this gap, an action plan was proposed to enhance the integration of educational websites, particularly in assessment practices, with stronger institutional support aligning with the goals of SDG 4: Quality Education.